Actual problems of criminological research of the identity of a juvenile offender - Daanov, Canpolad Ali Oqlu (Technium Social Sciences Journal, 2022)
Personality is a product of social relations and arises as a result of the interaction of social and psychological factors. Each person is distinguished by his attitude to certain values and the social image created by the influence of individual characteristics. Conceptual scientific research on personality has created a fertile ground for the study of scientific provisions in jurisprudence, especially in forensic research. With the help of criminological knowledge, the identity of the perpetrator is studied not only as a mechanical sum of social and psychological features. As the identity of the perpetrator is complex and multifaceted, the study should also be based on a detailed forensic analysis.